A bibliometric review of stakeholder theory in accounting: Current trends and future directions - Khomsiyah, Khomsiyah; Nilawati, Yuana Jatu; Aryati, Titik (Journal of Governance and Regulation, 2024)
In this study, a comprehensive bibliometric review of the stakeholder theory in accounting (both financial and managerial) is carried out. The bibliometric analysis provides historical information on research trends as well as research performance. This study explored the associated literature in stakeholder theory and accounting (economy, business, and management) from 1996–2022. The material was gathered from the Scopus database and analysed using VOSviewer and Tableau software. The documents that are based on previous research provide an analysis of the scientific output as well as the distribution of subject groups and journals. The authors’ chosen keywords have also been focused on identifying the most important areas of the study. The results of this research indicate that there has been an increase in the rate of yearly production across the time period that was investigated. The Journal of Business Ethics (JBE) is the most prolific journal and has published the most articles on stakeholder theory of any other publication. It is the top prolific journal. The outcome also demonstrates that the United States (U.S.) is home to a significant number of prestigious academic institutions. The U.S. tops the world in both the creation of scientific papers and the number of times those articles are mentioned in other documents. This study contributes on the awareness of using bibliometric analysis study to explore development in the scientific field. Bibliometric analysis study refers to the use of keywords to extract information for research growth in terms of the number of productions and citations. This study contributes on the awareness of using bibliometric analysis study to explore development in the scientific area.